Adaptation and Response in Drylands: A Dryland Research Agenda and Campaign Strategy - Andrew F. Feldman; Sasha C. Reed; Konrad Wessels; Dennis Ojima; David J. P. Moore; William K. Smith; Niall P. Hanan; Cibele Amaral; Flurin Babst; Joel A. Biederman; Marcy Litvak; Natasha MacBean; et al. (Global Change Biology, 2026)
Dryland ecosystems cover 41% of Earth's land surfaces, account for 44% of cultivated lands and 60% of food sources, and make large contributions to the global water and carbon cycles. However, these ecosystems are experiencing unprecedented extremes including heatwaves, floods, and droughts as well as hotter temperatures and often declining water resource availability. These ecosystems are some of the most challenging to monitor given their high temporal variability with rapid response to their environment as well as vast spatial variability with intermixing of different plant species and life forms amongst bare soil coverage. The Adaptation and Response in Drylands (ARID) campaign was selected by National Aeronautics and Space Administration (NASA) as a scoping study to develop a research agenda for a dryland field campaign. Here, we detail our ARID science research agenda and implementation plan that were developed based on an extensive community engagement effort in over 160 events with over a thousand scientists, land managers, and Tribal communities between 2023 and 2024. The selected science themes cover drought and climate variability, ecosystem structure, function, and biodiversity, carbon cycle interannual variability and trends, and social ecological systems (land management and adaptation). We then detail our remote sensing, modeling, and field‐based strategies to capture high temporal and high spatial resolution processes. Finally, our implementation strategy is presented which includes focus area selections in a core intensive western U.S. domain and distributed international domains. This strategy includes our overarching guiding principles of using multi‐temporal airborne acquisitions and super sites as well as enhancing land management in co‐development with end‐user partners. While originally developed for NASA, our ARID report creates a blueprint for any future dryland field campaign, at any scale, that can be implemented widely for foundational and applied science objectives.

A Temporally Explicit Production Efficiency Model for Fuel Load Allocation in Southern Africa - Christelle Hély; Kelly K. Caylor; Peter Dowty; Samuel Alleaume; Robert J. Swap; Hank H. Shugart; Christopher O. Justice (Ecosystems, 2007)

Nitrogen cycling in the soil–plant system along a precipitation gradient in the Kalahari sands - Julieta N. Aranibar; Luanne Otter; Stephen A. Macko; Chris J. W. Feral; Howard E. Epstein; Peter R. Dowty; Frank Eckardt; Herman H. Shugart; Robert J. Swap (Global Change Biology, 2004)
Nitrogen (N) cycling was analyzed in the Kalahari region of southern Africa, where a strong precipitation gradient (from 978 to 230 mm mean annual precipitation) is the main variable affecting vegetation. The region is underlain by a homogeneous soil substrate, the Kalahari sands, and provides the opportunity to analyze climate effects on nutrient cycling. Soil and plant N pools, 15 N natural abundance ( δ 15 N), and soil NO emissions were measured to indicate patterns of N cycling along a precipitation gradient. The importance of biogenic N 2 fixation associated with vascular plants was estimated with foliar δ 15 N and the basal area of leguminous plants. Soil and plant N was more 15 N enriched in arid than in humid areas, and the relation was steeper in samples collected during wet than during dry years. This indicates a strong effect of annual precipitation variability on N cycling. Soil organic carbon and C/N decreased with aridity, and soil N was influenced by plant functional types. Biogenic N 2 fixation associated with vascular plants was more important in humid areas. Nitrogen fixation associated with trees and shrubs was almost absent in arid areas, even though Mimosoideae species dominate. Soil NO emissions increased with temperature and moisture and were therefore estimated to be lower in drier areas. The isotopic pattern observed in the Kalahari ( 15 N enrichment with aridity) agrees with the lower soil organic matter, soil C/N, and N 2 fixation found in arid areas. However, the estimated NO emissions would cause an opposite pattern in δ 15 N, suggesting that other processes, such as internal recycling and ammonia volatilization, may also affect isotopic signatures. This study indicates that spatial, and mainly temporal, variability of precipitation play a key role on N cycling and isotopic signatures in the soil–plant system.

Spatial and temporal assessment of sources contributing to the annual austral spring mid‐tropospheric ozone maxima over the tropical South Atlantic - ROBERT J. SWAP; THOMAS A. SZUBA; MICHAEL GARSTANG; HAROLD J. ANNEGARN; LACKSON MARUFU; STUART J. PIKETH (Global Change Biology, 2003)
The primary source of the annual austral spring mid‐tropospheric ozone maxima over the tropical South Atlantic has generally been assumed to be biomass burning. However, ozone precursor emissions from biogenic, lightning, and anthropogenic sources in subequatorial Africa before and during the ozone peak are shown to be comparable, if not greater, in magnitude to regional biomass burning production. Moreover, an investigation of the spatial and temporal characteristics of these ozone precursor sources (i.e. vegetative and microbial activity, lightning‐induced generation, and anthropogenic emissions) suggests that these alternative sources can potentially make a substantial contribution to the seasonal ozone peak. This argument is supported by the practical limitations of atmospheric transport available to regionally produced ozone and ozone precursors.